Rapid profiling of G2 phase to mitosis progression by flow cytometry in asynchronous cells. Issue 21 (1st November 2020) - Sherman, John; Wang, Ruoning
ABSTRACT: The precise control of the cell cycle G2 phase to Mitosis (M phase) transition is central for cell fate determination. The commonly used methods for assessing G2 to M phase progression are based on synchronizing cells and involve perturbation of the natural cell cycle progression. Additionally, these methods are often time-consuming and labor-intensive. Here, we report a flow cytometry-based method that offers a kinetic analysis of G2 to M phase progression in asynchronous cells using nocodazole, 5-Ethynyl-2´-deoxyuridine staining, and histone H3 serine 28 phosphorylation (pH3) staining. Nocodazole is used to collect mitotic cells and prevent their progression into G1, at the same time EdU is added for use as a dump channel during analysis. The remaining cells can then be identified as either G1 or G2/M based on their DNA content. Finally, G2 and M phase cells can be separated based on a mitotic marker, phosphorylation of ser28 on histone H3. While developed to assay G2/M phase progression, this method also resolves G1/S phase progression with no additional steps other than analysis. Compared to double thymidine block, this method does not require extended pre-treatments and is compatible with a greater variety of cell lines, while at the same time offering enhanced consistency and temporal resolution.